The effect of project-based STAD cooperative learning on students’ mathematical literacy viewed from learning independence in linear programming - Hartono, Eko; Huda, Nizlel; Sudirman, Sudirman (Mahesa Research Center, 2025)
This study aims to determine the differences in mathematical literacy abilities between students at SMAN 17 Tebo taught using the Project-Based STAD Cooperative Learning Model and those taught using the conventional learning model, examine whether students with high learning independence taught using the Project-Based STAD Model have better mathematical literacy abilities than students with low learning independence taught using the conventional model, and identify the interaction between the Project-Based STAD Model and learning independence on students' mathematical literacy abilities. This research employs a quasi-experimental design with a population of 112 eleventh-grade students at SMAN 17 Tebo, with the sample randomly selected from two classes. The research instruments include a mathematical literacy test, a learning independence questionnaire, and an observation sheet on the implementation of the learning model. Data were collected through essay tests and analyzed using two-way ANOVA. The results indicate that the Project-Based STAD Cooperative Learning Model significantly improves students' mathematical literacy abilities compared to the conventional learning model, learning independence influences mathematical literacy, with students who have high learning independence performing better, and there is an interaction between the Project-Based STAD Model and learning independence in enhancing students' mathematical literacy abilities.